New Treatment Modalities in Hemophilia - Kaan Kavaklı (Trends in Pediatrics, 2022)
Hemophilia is a single gene disorder and as a genetical coagulation system problem it is a life-long bleeding disorder. Even though routine treatment modalities as plasma-derived and then recombinant factor concentrates available for last 50 years, unmet needs is continuing for hemophilia therapy. Gold standart treatment is regularly prophylactic FVIII/FIX infusions. However, life-long and frequent intra-venous infusions become medical burden for patients and families. New agents as enhanced half-life (EHL) factor concentrates and non-factor therapies which are able to be used subcutaneously are very hopeful. In this review, EHL factor concentrates, FVIII mimetic agents and re-balancing therapies will be discussed. Although celluler gene therapy is very hopeful and successful phase-3 studies are reported, gene therapy for hemophilia will not be mentioned in this review.